De exílio em exílio: um diálogo entre Eurípides e Clara de Góes na peça Medea en Promenade - Silva, Francisca Luciana Sousa da (2015)
This dissertation analyzes the unpublished text by Clara de Góes, Medea en Promenade (2012), based on the homonymous tragedy of Euripides' Medea (431 BC). The target text narrates the meeting of Glauce, (the young one), Medea (the woman) and the love of Medea (the old one), three women "in a sort of desert outside of time and space" according to the words of the author. Punctuating the speech of these women, the voice of Corifeu is perceived, often in the dark. Thus, we propose a critical reflection, turning our gaze to the protagonists of this poetic work, whose speeches are characterized by the following questions: "What is my place in exile? Do I belong to the exile ? "Such questions reinforce a longstanding demand of women, not only in Athens, but in many other places, especially the foreign ones. In order to understand these banks and the reason why there are so many crossings, many of them forced, we choose exile as a theme, considering it a object of interest not only of the Classics, but also of the cultural studies, for example. Our aim is to show, comparatively, how the so called "dialogue" between Euripides and Clara Garcia is constructed, trying also to discover another reading for the Medea myth, parallel or beyond the metaphor itself, concerning especially the heroin journeys. As pointed out by Jan Felix Gaertner, one of the authors that support our research, exile "has been one of the most productive literary themes in the literature of the twentieth century" (2007, p. 1) and has become a central theme in postcolonial literature or in association with another themes related to distance, separation, displacement, detachment and diaspora. Our hypothesis is to recognize the exile as a device, as Agamben would define (2009) – a key technical term in Foucault's thinking strategy, - not only a political device but also an existential one. All of this analysis, according to Medea, of Euripides, who immortalized her as an infanticide, but not without questioning her status as a foreign woman. In order to study this condition, we support ourselves especially in the works of Pierre Vidal - Naquet (1999) and Vernant (2009), Queiroz (1998) and Jasinski (2012). The following studies don’t seem to contradict our hypothesis, given their hybridization aspect: Sara Forsdyke (2005) and Gayatri C. Spivak (2014). The theoretical syllabus about the theater - from Greek tragedy to the contemporary scene – is based on the following works: Albin Lesky, Jacqueline Rommily, Marie - Claude Hubert and Patrice Pavis (2011).